Effect of auditory training and aided language stimulation on speech perception of children with hearing loss in Ibadan, Oyo State, Nigeria (2016)
Children fitted with hearing aid, without appropriate placement on aural rehabilitation always find it difficult to benefit maximally from the use of such assistive listening device as well as experiencing difficulty in producing intelligible speech sounds. Therefore, most of them become discouraged and not interested to undergo aural rehabilitation. Thus, this study examined the effect of auditory training (AT) and aided language stimulation (ALS), moderated on onset and degrees of hearing loss on the speech perception (detection, recognition and discrimination,) of children fitted with hearing aid in Ibadan, Oyo state, Nigeria. A pretest-posttest control group quasi-experimental research design, using a 3x2x2 factorial matrix, was adopted for the study. A purposive sampling technique was used to select 24 children (age ranged between 4 and 7 years) with hearing loss. The participants were randomly assigned to two treatment groups (AT and ALS) with a twelve-week intervention plan and a non-treatment control group. A standardised auditory trainer, and the Peabody Picture Vocabulary Test - 4th Edition (PPVT-4, r=.80 - .84), were the instruments used for the training. The five hypotheses formulated were tested at 0.05 level of significance, and data collected were analysed using Descriptive Analysis, Multivariate Analysis of Co- Variance (MANCOVA) and Scheffe Post Hoc Analysis. The findings revealed a significant main effect of treatments on the speech perception of the participants; Recognition (F 71.45, η = 94) Discrimination, (F = 88.11, η = .95) and Detection, (F = 32.06, η = 87), with ALS being a more significant treatment (Recognition (F = 3.37, p<.05); Discrimination (F= 5.25, p<.05) and Detection (F = 3.38, p<.05). The onset of hearing loss on the speech perception of the participants was significant in Recognition, (F = 9.37η=51), Discrimination, (F = 12.40η=57), and Detection, (F = 4.72η=39). The degrees of hearing loss had a significant effect on Recognition, (F = .020η=.002), Discrimination, (F = .032η=004), and Detection, (F = 4.31η=33), Treatments and onset of hearing loss interacted on Recognition (F = 4.24, η = .34); Discrimination, (F = 4.86, η = .39) and Detection, (F = 8.51, η = 65.);but no interaction between treatment and degree of hearing loss on Discrimination,(F= .73, p>.05); Recognition, (F = .83, p>.05), and Detection, (F = .96, p>.05) Onset of hearing loss interacted with the degrees of hearing loss on Detection, (F = 4.69, η = .39) but not on Recognition (F =.67, p>.05); and Discrimination, (F = .53, p>.05). Treatments, onset of hearing loss and degree of hearing loss interacted on Recognition (F =4.31, df = (1, 23), p<.05, η = .47; and Detection, F = 4.95, df = (1, 23), p<.05, η = .52. but not on Discrimination, F = .14, df = (1,23), p>.05). Based on the above findings, it is recommended that children with hearing loss should be rehabilitated using auditory training and aided language stimulation as part of the aural rehabilitative strategies meant to maximize the use of the assistive listening device.